Peran Perbankan Syariah dalam Mengimplementasikan Keuangan - Ferdi Pratama; Muhammad Subhan (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This study aimed to analyze the role of islamic banks in implementing financial inclusion in Indonesia. Financial inclusion is a process to provide formal financial access for the poor and low income people (unbankable people). This study was designed which approached qualitatively and quantitatively (mixed research). The qualitative data analyzed by using Straruss and Corbin’s theory consisted three major steps: open coding, axial coding, and selective coding. Quantitative analyzed by using comparative analysis of financial statements and financial ratio analysis such as CAR, ROA, ROE, NPF, and FDR period of 2010-2014. This study proved that Islamic banking had great potential in implementing financial inclusion, it was indicated by a significant increase in funding and financing since 2010-2014 and results of financial ratio analysis also shows the performance of Islamic banking and financial condition is good.